Accounting Scandals and Implications for Directors: Lesson from Enron - TAN, Pearl Hock Neo (Institutional Knowledge at Singapore Management University, 2006)
The essay analyzes the role and responsibilities of independent directors in the wake of accounting scandals such as Enron. It discusses the issue of whether independent directors should re-direct their focus to their roles as stewards rather than maximizers of corporate wealth. In particular, the essay uses a case-study approach to analyze risk factors that independent directors should be vigilant about in their role as corporate guardians.